Necroptotic cell binding of β2‐glycoprotein I provides a potential autoantigenic stimulus in systemic lupus erythematosus. Issue 9 (12th June 2019) - Salem, David; Subang, Rebecca; Pernet, Erwan; Divangahi, Maziar; Pineau, Christian; Cayrol, Romain; Levine, Jerrold S; Rauch, Joyce
Abstract: Systemic lupus erythematosus (SLE) is characterized by the development of autoantibodies against diverse self‐antigens with damage to multiple organs. Immunization with the SLE autoantigen β2 ‐glycoprotein I (β2 GPI) and lipopolysaccharide (LPS), a known trigger of necroptosis, induces a murine model of SLE. We hypothesized that necroptotic cells, like apoptotic cells, provide a "scaffold" of cellular self‐antigens, but, unlike apoptotic cells, necroptotic cells do so in a proinflammatory and immunogenic context. We demonstrate that β2 GPI indeed binds to necroptotic cells and serves as a target for anti‐β2 GPI autoantibodies. We further demonstrate that necroptotic, but not apoptotic, cells promote antigenic presentation of β2 GPI to CD4 T cells by dendritic cells. Finally, we show that β2 GPI/LPS‐immunized mice deficient in RIPK3 (receptor‐interacting serine/threonine‐protein kinase 3) or MLKL (mixed lineage kinase domain like), and consequently unable to undergo necroptosis, have reduced SLE autoantibody production and pathology. RIPK3 −/− mice had low levels of SLE autoantibodies and no renal pathology, while MLKL −/− mice produced low levels of SLE autoantibodies initially, but later developed levels comparable with wild type (WT) mice and pathology intermediate to that of WT and RIPK3 −/− mice. Serum cytokine levels induced by LPS tended to be lower in RIPK3 −/− and MLKL −/− mice than in WT mice, suggesting that impaired proinflammatory cytokine production may impact the initiation of autoantibody production in both strains. Our data suggest that self‐antigen (i.e. β2 GPI) presented in the context of necroptosis and proinflammatory signals may be sufficient to overcome immune tolerance and induce SLE. Abstract : Systemic lupus erythematosus (SLE) is characterized by the development of autoantibodies against diverse self‐antigens and damage to multiple organs. Immunization with the SLE autoantigen β2 ‐glycoprotein I (β2 GPI) and lipopolysaccharide, a known trigger of necroptosis, induces a murine model of SLE. We demonstrate that β2 GPI binds to both necroptotic and apoptotic cells, but that only necroptotic cells promote antigenic presentation of β2 GPI to CD4 T cells that provide help to multiple autoreactive B cells in SLE.